Microplastic Removal from Road Stormwater Runoff using Lab-scale Bioretention Cell - Fathiya Mufidah; Prayatni Soewondo (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
Microplastic removal from stormwater runoff from roads is necessary to reduce the effect of microplastic pollution in water bodies. Bioretention is a potential technology to remove microplastics in stormwater runoff from roads. A lab-scale experiment was conducted to determine the efficiency, effect on vegetation and discharge variation, and the kinetics of microplastic removal from stormwater runoff from roads using a bioretention cell. The experiment was done using an artificial sample based on visual characterization of stormwater runoff from highways, commercial, and residential roads. The vegetations that were examined were Vetivera sp. and Hibiscus sp. The operational discharge was varied based on rainfall intensity categories. The result showed that the removal efficiency was in the range of 92.4 to 99.3% with a mean of 97.2%. Statistical analysis (α = 5%) showed that variation in vegetation and discharge had no significant effect on microplastic removal using bioretention. The first-order kinetic analysis showed that the kinetic removal constant of the bioretention with Vetivera sp., bioretention with Hibiscus sp., and bioretention without vegetation was 0.0356, 0.034, and 0.0327, respectively. These results indicate that bioretention with Hibiscus sp. removed more microplastics at greater depths than with Vetivera sp.